The Law Applicable to the Implementation of the Judgment of International Bankruptcy - Jassim, Osama (Journal of Legal Sciences, 2022)
International bankruptcy is a legal system for those who take trade as a craft and stop performing their obligations of an international character as a result of a defect in their financial position. Legislative jurisdiction in cases of international bankruptcy is one of the most important topics of international bankruptcy by researching the position of national and comparative legislation by determining the applicable law such as the law of the court that hears the dispute or the law to which the attribution rule refers.